Synthesis and Characterization of Pelletized Coke with Tar Impregnation from Carbonization of Palm Kernel Shells as Nickel Laterite Reductant - Hariyadi, Asful; Nurjaman, Fajar; Rohimsyah, Fikan Mubarrok; Nafisah, Azmia Rizka; Hidayat , Jefri Pandu (ASEAN Journal of Chemical Engineering, 2025)
The nickel laterite beneficiation policy supports the domestic stainless and alloy steel industries. However, reliance on imported coke for smelting remains a major challenge. The main challenge is the dependence on imports of reductant coke for the smelting process. Palm kernel shell (PKS) is a promising alternative that aligns with the carbon-neutral concept, but its pyrolyzed carbon shows low calorific value and mechanical strength for metallurgical use. This study aims to produce biocoke by converting PKS into carbon–carbon (C/C) composites using its carbon and tar products to enhance mechanical and thermoplastic properties. This study aims to produce biocoke by converting PKS into carbon–carbon (C/C) composites using its carbon and tar products to enhance mechanical and thermoplastic properties. Initial KOH activation (impregnation mass ratio 0.5) created a porous structure for tar deposition. Briquetting (30×30 mm) followed by co-carbonization (250 °C, 1 h) was conducted at various char-to-tar mass ratios. The best condition was achieved at a tar ratio of 1:2, producing composites with high fixed carbon (88.17%), low volatile matter, and compressive strength suitable for metallurgical applications. SEM analysis confirmed uniform carbon fiber distribution within the matrix. The final product also met ASTM D3173 standards with a heating value of 7,328 kcal/kg. XRD analysis of limonite ore reduction using this biocoke showed a decrease in geothite and lizardite phases and the formation of metallic phases such as Fe-Ni alloy, FeS, and wustite, especially at 900 °C and 1100 °C. These results indicate effective metallothermic reduction. C/C composite from PKS offers a sustainable, high-performance alternative to commercial coke for nickel laterite reduction, fulfilling both energy and environmental considerations.